Searching for Roots of Entrainment and Joint Action in Early Musical Interactions - Phillips-Silver, Jessica; Keller, Peter (Frontiers in Human Neuroscience, 2012)
When people play music and dance together, they engage in forms of musical joint action that are often characterized by a shared sense of rhythmic timing and affective state (i.e., temporal and affective entrainment). In order to understand the origins of musical joint action, we propose a model in which entrainment is linked to dual mechanisms (motor resonance and action simulation), which in turn support musical behavior (imitation and complementary joint action). To illustrate this model, we consider two generic forms of joint musical behavior: chorusing and turn-taking. We explore how these common behaviors can be founded on entrainment capacities established early in human development, specifically during musical interactions between infants and their caregivers. If the roots of entrainment are found in early musical interactions which are practiced from childhood into adulthood, then we propose that the rehearsal of advanced musical ensemble skills can be considered to be a refined, mimetic form of temporal and affective entrainment whose evolution begins in infancy.